Applications of camphor-derived chiral auxiliaries in the asymmetric synthesis of Î±-amino acids and other systems - Matjila, Joseph Moemise (Rhodes University, Faculty of Science, Department of Chemistry)
A viable synthetic route to camphor-derived imino lactones as precursors for the asymmetric synthesis of a-amino acids has been established. Several synthetic strategies have been investigated and the required regioisomeric imino lactones were finally obtained via the step-wise condensation of JV-(carbobenzyloxy)glycine with the a-ketols, 3-exo-hydroxycamphor and 2-exo- hydroxy-3-bomanone. Enolates of the camphor imino lactones, generated using potassium tert- butoxide, were reacted with a range of alkyl halides. Dialkylation was observed using the 2-imino lactone, while the regioisomeric 3-imino lactone derivative gave monoalkylated products with diastereoselectivities, shown by NMR spectroscopy, to range from 43% d.e. for the methylated product to > 99% d.e. for larger alkyl groups. The expected preference for endo-alkylation is supported by NMR (chemical shift, coupling constant and NOE) data and was confirmed by acidic hydrolysis of the pentylated 3-imino lactone to afford the known acid. Computer modelling, with the software package HYPERCHEMÂ®, was used to explore the conformational properties of the alkylated products and their enolate precursors. Exploratory work on the enantiomeric beneficiation of racemic amino acids, using alkylated imino lactone derivatives, revealed preferential exo-protonation of the enolate intermediates. Asymmetric Baylis-Hillman reactions between a novel camphor-derived acrylic ester and a range of aldehydes afforded the corresponding 2-(hydroxyalkyl)acrylates in up to 59% d.e., the observed stereoselectivities being sensitive to both steric and electronic factors. Attempts to prepare imino lactone derivatives from ketopinic acid, although unsuccessful, led to the isolation of two novel W-(carbobenzyloxy)glycinates, whose structures were established by 1- and 2-D NMR spectroscopy. Attempts to prepare "BINAP" analogues from dibomyl ether's also proved unsuccessful, but the investigation led to the discovery of a third, novel dibomyl ether.
Keywords: Imino compounds; Alpha-amino acid; Asymmetric synthesis; Camphor; Enantioselective catalysis; Baylis-Hillman reaction